Upaya Gastrodiplomasi Indonesia di Korea Utara - Johanna Imanuella; Maria Indira Aryani (Jurnal Hubungan Internasional, 2020)
History has recorded the crucial role of food in life. More than just abasic human need, food can be a unifying and dividing society, furtherdemonstrating its crucial role in civilization. This led to the emergenceof the practice of gastrodiplomacy — a practice of cross-border culturaldiplomacy through food. Indonesia is one of the countries that haspracticed gastrodiplomacy by empowering its culinary pride. One of thedestinations for Indonesian gastrodiplomacy is North Korea. On variousoccasions, the Embassy of the Republic of Indonesia in Pyongyang has oftenpromoted Indonesian food through cooking demonstrations, bazaars,or various formal banquets. Besides, Indonesia has also opened its firstIndonesian product outlet in Pyongyang, which markets Indonesian foodproducts. This article aims to show Indonesia’s gastrodiplomacy efforts inNorth Korea and map them based on various gastrodiplomacy campaignstrategies.